Lisp and its impact on the entry of some words into the Arabic lexicon - Al-Saeedi, Ass.Prof Dr . Qassem Muhammad Kamel (Thi Qar Arts Journal, 2022)
In many collections of language, there are some expressions that are indicated as melody, error, bad language, language, etc., and among them what is indicated as a lisp. They often mention that, doubting it, and they are not sure about it, and I tried in this research. To collect the texts in which lisping is referred to, and refer them to the texts of the language, after referring to the most famous of her books, the most extensive and the most comprehensive, in order to explain its impact on the entry of some words into the lexicon, and what is the truth about that? What is the space occupied by Arabic dictionaries? After categorizing what has reached us of it into four groups, it includes the lisp of children, the natural lisp that afflicts the human tongue during its youth and after it, and the occasional lisp of people of advanced age and the like of those whose teeth have fallen out, or some of them, and the lisp of non-Arabs who do not know the sounds of Arabic. Their tongues were not accustomed to uttering it, after emphasizing the well-known in the lisp of each of them, which was indicated by the books of the previous ones, so that we could distinguish between one lisp and another on a scientific basis. To explain its impact on the language, was it broad and extended, or narrow and limited, including limited expressions, that do not include everything that has reached us about them? So the research studied each word separately, and then came to the conclusion that it is a language or a lisp, and perhaps something else, or both are possible based on the laws of phonetic substitution, both of which are substitution, but the phonetic substitution takes place according to the laws of phonetics because of the participation of the two sounds in the director, or the adjective , or their convergence, as for the lisp, it is caused by an emergency replacement; This is due to the inability of the tongue to produce the sound from its correct outlet due to a problem with the articulation apparatus, so it diverges to a place close to it or similar to it.